Citri Reticulatae Pericarpium extract and flavonoids reduce inflammation in RAW 264.7 macrophages by inactivation of MAPK and NF‐κB pathways. Issue 4 (29th July 2022) - Zhang, Xutao; Zhou, Yan; Cheong, Meng Sam; Khan, Haroon; Ruan, Cheng‐Chao; Fu, Manqin; Xiao, Jianbo; Cheang, Wai San
Abstract: Citri reticulatae Pericarpium (CRP) is widely consumed as a food and herbal medicine in various countries and has many biological activities, including anti‐inflammatory effects, but the molecular mechanism is not completely known. This study aims to investigate whether CRP extract and its major flavonoids hesperidin (Hsd) and hesperetin (Hst) can reduce inflammation in macrophages and the underlying mechanism. The chemical composition of CRP was detected by ultra‐performance liquid chromatography‒mass spectrometry (UPLC‒MS) analysis. The inflammatory cell model was induced by stimulating RAW 264.7 cells with lipopolysaccharide (LPS, 1 μg/ml). Levels of nitric oxide (NO) and cytokines were determined by Griess assay and enzyme‐linked immunosorbent assay kits, respectively. Protein expressions were examined by western blotting. CRP extract dose‐dependently suppressed LPS‐induced production of NO, interleukin‐6 (IL‐6), and tumor necrosis factor‐α. Elevated expressions of inducible NO synthase (iNOS) and cyclooxygenase‐2 (COX‐2) and phosphorylation of c‐Jun NH2 ‐terminal kinase, extracellular signal‐regulated kinase, p38, and p65 in LPS‐stimulated cells were prevented by CRP extract. Hsd and Hst are flavonoids present in CRP, as confirmed by UPLC‒MS analysis. Both Hsd and Hst ameliorated LPS‐triggered inflammation to reduce NO release, IL‐6 generation, and protein expressions of iNOS and COX‐2. These results reveal that CRP extract possesses anti‐inflammatory activity by inactivating the mitogen‐activated protein kinase and nuclear factor kappa‐light chain‐enhancer of activated B cells pathways, where Hsd and Hst are bioactive constituents, implying the potential application of CRP as dietary supplements against inflammatory diseases. Graphical Abstract: Citri reticulatae Pericarpium extract reduces inflammation through the inhibition of mitogen‐activated protein kinase and nuclear factor kappa‐light chain‐enhancer of activated B cells pathways in RAW264.7 macrophages.